Penanaman akhlak pada anak usia dini pasca pandemi covid-19 melalui metode storytelling - Laili, Zuhrotul; Suryono, Suryono; Nursikin, Mukh (Indonesian Journal of Muhammadiyah Studies (IJMUS), 2022)
ABSTRACT In the process of teaching and learning activities, of course, a teacher uses various methods in carrying out his duties. The method used to be more effective, communicative, and fun for children, must be in line with the stages of development, both in terms of language, media and implementation. One method that is considered suitable for instilling moral values ​​in children is the storytelling method. With storytelling children can capture the narrative told by the teacher and apply it to their daily lives. The storytelling method in inculcating moral values ​​that is applied has a lot of positive effects on the moral development of children. The type of research used is qualitative research. The subjects of this study were children aged 4-5 years old. Qualitative research, which is a method of collecting data with the author directly in the field, is used to collect data in this study. Therefore, the information collected is empirical. The writer then used the following data collection procedures in this field study: 1) Observation 2) Conducting interviews 3) Providing documentation. This study uses three analytical techniques: data reduction, data display (data presentation), and conclusion drawing (data verification). The purpose of this study was to examine the use of the storytelling method in growing morals, as well as the supporting elements and challenges of using the storytelling method in fostering good behavior in children. The implementation is carried out through the stages of planning, implementation, and evaluation. The application of the method at the same time in the context of inculcating moral values ​​in children. With the Storytelling method used by researchers to instill morals in early childhood, the results are significant. Keywords: Storytelling, Morals, Learning Method